Flexural-torsional behaviour of steel reinforced concrete members subjected to repeated loading. - Hsu, H.L (Earthquake engineering & structural dynamics.)
This paper presents an experimental investigation of the inelastic behaviour of steel reinforced concrete (SRC) members under cyclically applied bending and torsional loading. Fourteen steel reinforced concrete members made from three structural steel sections with different cross sectional properties were tested under various combinations of bending and torsion. Results indicate that the ultimate flexural capacity of an SRC member was significantly reduced under a moderate degree of torsion. Based on these findings, a quantitative evaluation of the effect of torsion was made and a simplified interaction curve between bending and torsion is proposed.